Structural evaluation of defects in β-Ga2O3 single crystals grown by edge-defined film-fed growth process. (14th November 2016) - Ueda, Osamu; Ikenaga, Noriaki; Koshi, Kimiyoshi; Iizuka, Kazuyuki; Kuramata, Akito; Hanada, Kenji; Moribayashi, Tomoya; Yamakoshi, Shigenobu; Kasu, Makoto
Abstract: We have structurally evaluated β-Ga2 O3 crystals grown by edge-defined film-fed growth process using etch pitting, focused ion beam scanning ion microscopy, transmission electron microscopy, and related techniques. We found three types of defects: arrays of edge dislocations corresponding to etch pit arrays on -oriented wafers, platelike nanopipes corresponding to etch pits revealed on the (010)-oriented wafers, and twins including twin lamellae.